Integration of microalgae-based bioenergy production into a petrochemical complex: Techno-economic assessment - Gonçalves, AL (2016)
The rapid development of modern society has resulted in an increased demand for energy, mainly from fossil fuels. The use of this source of energy has led to the accumulation of carbon dioxide (CO2) in the atmosphere. In this context, microalgae culturing may be an effective solution to reduce the CO2 concentration in the atmosphere, since these microorganisms can capture CO2 and, simultaneously, produce bioenergy. This work consists of a techno-economic assessment of a microalgal production facility integrated in a petrochemical complex, in which established infrastructure allows efficient material and energy transport. Seven different scenarios were considered regarding photosynthetic, lipids extraction and anaerobic digestion efficiencies. This analysis has demonstrated six economically viable scenarios able to: (i) reduce CO2 emissions from a thermoelectric power plant; (ii) treat domestic wastewaters (which were used as culture medium); and (iii) produce lipids and electrical and thermal energy. For a 100-ha facility, considering a photosynthetic efficiency of 3%, a lipids extraction efficiency of 75% and an anaerobic digestion efficiency of 45% (scenario 3), an economically viable process was obtained (net present value of 22.6 million euros), being effective in both CO2 removal (accounting for 1.1 × 104 t per year) and energy production (annual energy produced was 1.6 × 107 kWh and annual lipids productivity was 1.9 × 103 m3). (c) 2016 by the authors.